2021
DOI: 10.1017/jfm.2021.116
|View full text |Cite
|
Sign up to set email alerts
|

Instability of a shear-imposed flow down a vibrating inclined plane

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…At the fluid surface, , transport of insoluble surfactant induces a Marangoni stress, which is balanced by the hydrodynamic stress of the mainstream fluid. This fact yields the following tangential and normal stresses dynamic boundary conditions for the shear-imposed surfactant-laden fluid flowing down a compliant inclined plane (Blyth & Pozrikidis 2004; Wei 2005; Samanta 2014 a , b ; Bhat & Samanta 2018, 2019; Samanta 2021) where is the ambient pressure, and is the surface tension of the mainstream fluid, which alters linearly with the surfactant concentration by the following relation: where is the constant base surface tension when surfactant concentration keeps its constant base value . It should be useful to mention here that surface elasticity, , is positive because the surface tension of the mainstream fluid reduces with an increasing value of surfactant concentration.…”
Section: Mathematical Formulationmentioning
confidence: 98%
See 1 more Smart Citation
“…At the fluid surface, , transport of insoluble surfactant induces a Marangoni stress, which is balanced by the hydrodynamic stress of the mainstream fluid. This fact yields the following tangential and normal stresses dynamic boundary conditions for the shear-imposed surfactant-laden fluid flowing down a compliant inclined plane (Blyth & Pozrikidis 2004; Wei 2005; Samanta 2014 a , b ; Bhat & Samanta 2018, 2019; Samanta 2021) where is the ambient pressure, and is the surface tension of the mainstream fluid, which alters linearly with the surfactant concentration by the following relation: where is the constant base surface tension when surfactant concentration keeps its constant base value . It should be useful to mention here that surface elasticity, , is positive because the surface tension of the mainstream fluid reduces with an increasing value of surfactant concentration.…”
Section: Mathematical Formulationmentioning
confidence: 98%
“…A detailed study of linear stability analysis is carried out in the arbitrary wavenumber regime. The motivation is to understand the dynamics of interfacial wave for a liquid lining flow in a pulmonary airway occlusion process where airflow moves back and forth during breathing and exerts a shear stress on the air-liquid interface (Halpern & Grotberg 1993;Wei 2005;Samanta 2020b). In addition, the purpose is to investigate the interactions between flowing fluid and wall flexibility on the shear-induced Marangoni instability that generally occurs in pulmonary airways.…”
Section: Introductionmentioning
confidence: 99%
“…To address this research gap, this paper introduces the slanting slit flow theory and divides the nonparallel channel into two parts: parallel plate and slanting plate [43,44]. Based on these two parts of the flow theory, an asymmetric theoretical model applicable to non-Newtonian fluids in non-parallel plates is developed using an analytical superposition method.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that the time scale of the flow evolution is much larger than the period of substrate oscillation, and it is reported that all periodic and solitary-wave solutions are unstable, regardless of their parameters. For an inclined vibrating plane, the linear stability of a shear-imposed viscous flow is deciphered for disturbances of arbitrary wavenumbers to investigate the effect of imposed shear stress on Faraday instability (Samanta 2021).…”
Section: Introductionmentioning
confidence: 99%